Intervensi Psikoedukasi Dapat Menurunkan depresi pada Pasien Kanker - Dewi Handayani; Yati Afiyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the effect of psychoeducational interventions on cancer patients who experience depression. The method used was a systematic literature search from randomized controlled trials conducted from 2 September 2022 to 7 September 2022, using Clinical Key Nursing, Embase, Proquest, and Science Direct databases. The results showed that the psychoeducational intervention in the included studies showed a beneficial effect on cancer patients with depression as assessed before the intervention and after using the Patient Health Questionnaire-8 (PHQ-8), Distress Thermometer, and Hospital Anxiety & Depression Scale (HADS). ). The five articles reviewed obtained statistical data on psychological outcomes, namely depression, from P <0.05-0.95. The psychoeducational interventions provided by the five articles are MBST (Mindfulness Based Swinging Technique), iCanDo, LTLWC (Learning to Live with Cancer), iCARE, and MINDCAN, which combine lecture-based education, skills practice, discussion, and counseling. Psychoeducational interventions are carried out online and offline by a team of health professionals. Five studies reported a significant effect in reducing depression in cancer patients. In conclusion, preliminary evidence suggests that psychoeducational interventions have beneficial effects and can relieve depression in cancer patients. Keywords: Depression, Psychoeducational Intervention, Cancer